2015
DOI: 10.1002/phar.1669
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Safety of Adenosine and Regadenoson in Patients Undergoing Outpatient Cardiac Stress Testing

Abstract: Among patients undergoing an outpatient pharmacologic stress test, the use of adenosine was associated with a lower occurrence of adverse effects and lower rate of a rescue agent use and may provide a potential medication cost savings opportunity compared with regadenoson.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 12 publications
2
14
0
Order By: Relevance
“…Across different pharmacological stressors, regadenoson and dobutamine showed an increased likelihood when compared to adenosine. In line with the recent literature, adverse event rates were higher among regadenoson and limited to mild and moderate events, mainly dyspnea [ 24 , 25 ]. This difference could be attributed to the pharmacokinetic properties of regadenoson with a comparably long, tri-phasic half-life time [ 23 ].…”
Section: Adverse Events Risk Factorssupporting
confidence: 87%
“…Across different pharmacological stressors, regadenoson and dobutamine showed an increased likelihood when compared to adenosine. In line with the recent literature, adverse event rates were higher among regadenoson and limited to mild and moderate events, mainly dyspnea [ 24 , 25 ]. This difference could be attributed to the pharmacokinetic properties of regadenoson with a comparably long, tri-phasic half-life time [ 23 ].…”
Section: Adverse Events Risk Factorssupporting
confidence: 87%
“…Though studies have shown that regadenoson is equivalent to adenosine with regards to FFR testing, there are significant cost differences between these pharmacological agents. Regadenoson with aminophylline is likely to be more expensive when compared to adenosine based on average wholesale pricing; however, the utility of regadenoson extends beyond cost alone. Although aminophylline is a safe and effective reversal agent for regadenoson, most patients would not require reversal given regadenoson's limited side effect profile.…”
Section: Discussionmentioning
confidence: 99%
“…Safety profile with no significant difference compared to adenosine [47] Capadenoson (partial A 1 AdR agonist) Reduced bradycardic adverse effects in preclinical models and no effect on heart rate in clinical studies [91] 2-CI-IB-MECA (selective A 3 AdR agonist) Impairment of oligodendrocytes through generation of ROS and mitochondrial membrane depolarization [51] Caffeine (non-selective AdR antagonist) Symptoms and signs of acute intoxications vary from weakness, vomiting, fever and seizure to life-threatening cerebral oedemas, arrhythmias, electrolyte disturbances and death [64] Chronic exposure leads to caffeine tolerance and after termination of consumption typical withdrawal symptoms occur [60] Developmental toxicity and influences on lactation performance were reported in studies on experimental animals. Genotoxicity was demonstrated on lower organisms such as bacteria, fungi etc [30,[71][72][73][74] Rolofylline (selective A 1 AdR antagonist) Increased frequency of seizures and strokes in treated patients [22] 2-Amino-4-phenyl-8-pyrrolidin-1-ylmethyl-indeno [1,2-d]pyrimidin-5-one (dual acting A 2A AdR and A 1 AdR antagonist)…”
Section: Inhibition Of Adenosine Kinasementioning
confidence: 99%
“…A 2A AdR selective agonists, like regadenoson and apadenoson, were developed to overcome adverse effects of adenosine in patients undergoing cardiac stress testing due to its non‐selective activity. Many clinical trials have been conducted to compare the safety profile of regadenoson and adenosine; however, there were no significant improvements in reducing frequencies of adverse effects . Recently, it has been shown that A 2A AdR activation increases blood–brain barrier permeability, which could be suitable for drug delivery into brain or could on the other side pose a risk for different chemicals to reach CNS …”
Section: Adverse Effects and Toxicity Of Adenosine Receptor Ligandsmentioning
confidence: 99%
See 1 more Smart Citation